As origens gregas do racionalismo popperiano - Provetti Junior, José (2014)
This dissertation proposes to present the results of a survey around the philosophical foundations of popperian view of knowledge, because assumed through the work of Popper: The world of Parmenides: essays on the presocratic illustration (TWP), the idea of returning to the Greeks as regards the originated attitude of these as philosophy. Initiators of discursive rational mode opened in Archaic Hellas, and that proved the source of the rich array of later scientific and rational development. Popper raises the question of criticism of the inductive method of science positivism, locating it historically in what he called baconian myth , as a certain Aristotle's bias to create the inductive method based on the socratic elencho. It is supposed to understand the relevance of Popper's invitation to return as the Greeks and their originates motivation on the cosmology and the theory of knowledge by being able to better understand popperian logic of scientific inquiry; investigating the historical and philosophical foundations of his argument as it is believed, is set directly on the shaft of the presocratic thought. What make possible to understand the whole popperian work as the philosopher's attempt to build a truly foundational cosmological system, aligned with the archaic Hellenic philosophizing, aiming the challenges of contemporary philosophy and science with respect to Epistemology.